Does Sharia Audit Quality Strengthen Maqasid-Based Performance in Indonesian Islamic Banks? - Mutia Pamikatsih; M Adhitya Wardhana; Nashirotun Nisa Nurharjanti; Toto Sugihyanto; Fadilla Muhammad Mahdi; Eko Sudarmanto (The Es Accounting And Finance, 2026)
This study investigates the influence of Sharia audit quality on Maqasid-based performance in Indonesian Sharia banks from the perspective of customers. The study adopts a quantitative explanatory research design using primary data collected from 100 customers of Indonesian Sharia banks through a structured questionnaire based on a five-point Likert scale. Purposive sampling was employed to select respondents who had sufficient experience using Islamic banking services. Data were analyzed using SPSS version 25, including descriptive statistics, validity and reliability tests, classical assumption tests, simple linear regression analysis, coefficient of determination (R²), and hypothesis testing using the t-test. The findings indicate that all measurement items are valid and reliable, with Cronbach's Alpha values of 0.889 for Sharia audit quality and 0.901 for Maqasid-based performance. The regression analysis reveals that Sharia audit quality has a positive and statistically significant effect on Maqasid-based performance (β = 0.713; t = 10.488; p < 0.001). Furthermore, the coefficient of determination (R² = 0.528) indicates that Sharia audit quality explains 52.8% of the variation in Maqasid-based performance. These findings suggest that competent, independent, and effective Sharia auditing enhances transparency, accountability, ethical governance, and compliance with Islamic principles, thereby strengthening the achievement of Maqasid al-Shariah within Indonesian Islamic banking institutions. This study contributes to the Islamic banking literature by providing empirical evidence that strengthening Sharia audit practices is essential for improving governance quality and reinforcing customer confidence in achieving Maqasid-oriented organizational performance.